Investigation On Effects Of Arfoil Variation In A Slotted Propeller - Ravindran, Nirresh Prabu (Universiti Sains Malaysia, 2019)
The usage of slots has gained renewed interest in aerospace particularly on propeller design. Most of the works have focused on improving the aerodynamic performance and efficiency. Modern research on propeller design aims to design propellers with high thrust performance under low torque conditions without any weight penalty. This paper discussed computational fluid dynamics method to predict propeller performance for a small scale propeller. In addition, the performance of the slotted blade designs is presented, in terms of thrust coefficient, power coefficient and efficiency. The performance of slotted propeller blade is influence by the different types of airfoils being used on the blade. Thus, the shape of the slot is fixed which is a square shaped slot and the position of the slot is also fixed at 62.5% of the Chord length. Although research on slotted design has been done before, none has been done for different Airfoils on the propeller blade. Thus, this study aims to provide an extensive research on slotted propeller design with different Airfoils of different properties such as high Reynolds number, low Reynolds number, symmetrical, asymmetrical high lift and low drag. The basis for the propeller will be the APC Slow Flyer. The flow simulations are performed through three-dimensional computational fluid dynamic software (ANSYS Fluent) to determine the thrust coefficient, power coefficient and overall efficiency measured in advancing flow conditions.